Chicken Eggshell Membrane and Cuticle: Insight from Bioinformatics and Proteomics - Du, Jingwen (Université d'Ottawa / University of Ottawa, 2013)
The chicken eggshell possesses physical and chemical barriers to protect the embryo from pathogens. The avian eggshell cuticle is the outmost layer of the eggshell whose protein constituents remain largely unknown. Since eggs with incomplete or absent cuticle are more susceptible to bacterial contamination, we hypothesize that cuticle protein components play an important role in microbial resistance. In our study, at least 47 proteins were identified by LC/MS/MS in the non-calcified cuticle layer. Similar to Kunitz-like protease inhibitor (also annotated as ovocalyxin-25, OCX-25) and ovocalyxin-32 (OCX-32) were two of most abundant proteins of the cuticle proteins. Some proteins that have antimicrobial activity were also detected in the proteomic results, such as lysozyme C, ovotransferrin, ovocalyxin-32, cystatin, ovoinhibitor. This study represents the first comprehensive report of the cuticle proteome. Since the sequence similarity of the kunitz motif in OCX-25 is similar to that of BPTI, it is predicted that it will have the same trypsin inhibitory and antimicrobial activity against Gram-positive and/or Gram-negative bacteria. In order to test the antimicrobial property and trypsin inhibitor activity of OCX-25, cuticle proteins were extracted by 1N HCl. Antimicrobial activity was monitored using the Bioscreen C instrument; and antimicrobial activity was identified primarily against Staphylococcus aureus. Trypsin inhibitor activity was studied by using a specific trypsin assay, and the assay indicated that the cuticle proteins could inhibit the reaction of trypsin and substrate. Therefore, the current research has provided some insight into the antimicrobial and enzymatic aspects of the cuticle proteins, and its function for egg protection. Eggshell membranes are another important component of the chicken eggshell.Due to its insoluble and stable properties, there are still many questions regarding formation and constituents of the eggshell membranes. The purpose of our study was to identify eggshell membrane proteins, particularly these responsible for its structural features, by examining the transcriptome of the white isthmus during its formation. Bioinformatics tools were applied to analyze the differentially expressed genes as well as their encoded proteins. Some interesting proteins were encoded by the over-expressed genes in the white isthmus during the formation of eggshell membranes, such as Collagen X, and similar to spore coat protein SP75. These proteins may have potential applications. Our study provides a detailed description of the chicken white isthmus transcriptome during formation of the eggshell membranes; it could lead to develop the strategies to improve food safety of the table egg.
Keywords: eggshell cuticle; eggshell membrane; similar to spore coat protein SP75; Collagens; proteomics; bioinformatics